PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA PEGAWAI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) - Endarwita; Mai Yuliza; Mela Hartina (SOSIOEDUKASI, 2021)
This research was conducted at Employment and Human Resources Development Agency (BKPSDM) West Pasaman. The purpose of this study was to determine the impactof Communication and Work Environment on Work Performance ofEmployment and Human Resources Development Agency (BKPSDM) employees. The population of this study were all employees of Employment and Human Resources Development Agency (BKPSDM) West Pasaman, namely 55 people. For the population is below 100 people, the sampling technique used saturated sample; the entire population is sampled. The data collection methods used questionnaires and interviews. The data analysis method used descriptive analysis and multiple linear regression using SPSS 16.00. The results of this study indicate a relationship between independent variable and dependent variable. It can be explained that communication variable has positive and insignificant impact on work performance with regression coefficient of 0.797 and significant rate of 0.429 (> 0.05). Work environment has positive and significant impact on work performance with regression coefficient of 0.038 and significant rate of 0.004 (<0.05). Communication and work environment simultaneously have positive and significant impact on work performance with regression coefficient of 43.322 and significant rate of 0.000 (<0.05). The value of R² shows 62.5% and the remaining 37.5% is influenced by other variables.